Exogenous Melatonin Modulates Physiological Response to Nitrogen and Improves Yield in Nitrogen-Deficient Soybean (Glycine max L. Merr.) - Wang, Huamei; Ren, Chunyuan; Cao, Liang; Zhao, Qiang; Jin, Xijun; Wang, Mengxue; Zhang, Mingcong; Yu, Gaobo; Zhang, Yuxian (Frontiers in Plant Science, 2022)
Melatonin (MT) is a key plant growth regulator. To investigate its effect at different growth stages on the yield of soybean under nitrogen deficiency, 100 μM MT was applied to soybean supplemented with zero nitrogen (0N), low nitrogen (LN), and control nitrogen (CK) levels, during the plant vegetative growth (V3) and filling (R5) stages. This study revealed that the application of MT mainly enhanced the nitrogen fixation of plants by increasing the root nodule number and provided more substrates for glutamine synthetase (GS) under 0N supply. However, under the LN supply, more ammonium was assimilated through the direct promotion of nitrate reductase (NR) activity by MT. MT enhanced the activity of ammonium-assimilation-related enzymes, such as GOGAT and GDH, and the expression of their coding genes, promoted the synthesis of chlorophyll and amino acids, and increased the photosynthetic capacity under nitrogen deficiency. Exogenous MT directly upregulated the expression of genes involved in the photosynthetic system and stimulated dry-matter accumulation. Thus, MT alleviated the inhibitory effect of nitrogen deficiency on soybean yield. This mitigation effect was better when MT was applied at the V3 stage, and the seed weight per plant increased by 16.69 and 12.20% at 0N and LN levels, respectively. The results of this study provide a new theoretical basis to apply MT in agriculture to improve the resilience of soybean plants to low nitrogen availability.